2011
DOI: 10.3390/molecules16021418
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient and Safe O-Methylation of Flavonoids with Dimethyl Carbonate (DMC)

Abstract: Dietary flavonoids exhibit beneficial health effects. Several epidemiological studies have focused on their biological activities, including antioxidant, antibacterial, antiviral, anti-inflammatory and cardiovascular properties. More recently, these compounds have shown to be promising cancer chemopreventive agents in cell culture studies. In particular, O-methylated flavonoids exhibited a superior anticancer activity than the corresponding hydroxylated derivatives being more resistant to the hepatic metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 30 publications
3
32
0
1
Order By: Relevance
“…Finally, our rationally designed pathway can serve as a framework for improvement of Avn production using combinatorial approaches that have been shown previously to increase tyrosine production [58]. As an adjunct to the recent development of procedures that use safe methylating agents [59], this study describes a basis for eco-friendly production of cinnamoyl anthranilates such as Avn D and Avn F and can serve as a scaffold for the synthesis of more elaborate molecules such as tranilast and its analogs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our rationally designed pathway can serve as a framework for improvement of Avn production using combinatorial approaches that have been shown previously to increase tyrosine production [58]. As an adjunct to the recent development of procedures that use safe methylating agents [59], this study describes a basis for eco-friendly production of cinnamoyl anthranilates such as Avn D and Avn F and can serve as a scaffold for the synthesis of more elaborate molecules such as tranilast and its analogs.…”
Section: Discussionmentioning
confidence: 99%
“…Eupalitin is one of the O‐methylated flavonols that has been detected in Ipomopsis aggregata (Smith et al, ). Study has reported that O‐methylated flavonoids exhibited increased cancer chemopreventive properties than the corresponding hydroxylated derivatives of molecules (Bernini et al, ). At the cancer promotion stage, methylated flavones inhibited the proliferation of cancer cells, but not normal cells, with greater potency than the unmethylated flavones (Walle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methylation of phenolic compounds significantly increases their ability to be transported across biological membranes, making them more stable to metabolic changes; this can also increase their biological efficacy, particularly its antitumor activity in cell culture studies. In this sense, O-methylated flavonoids exhibited a superior anticancer activity than the corresponding hydroxylated derivatives in cell culture studies, being more resistant to the hepatic metabolism and showing a higher intestinal absorption 49 . Moreover, methylated flavonoids showed effects on transport proteins which play a central role in the defense of organism against toxic compounds (multidrug resistance proteins) 50 .…”
Section: Acetylation and Methylationmentioning
confidence: 98%